Women in the Police Academy: A National-Level Exploration of the Gendered Nature of Non-Completion - Paoline, Eugene A. (Women & criminal justice, 2024)
The underrepresentation of women in policing is well documented as are efforts to understand the disparity. Some of these efforts have examined the first point newly hired women experience occupational socialization: basic law enforcement training at police academies nationwide. Largely absent from this line of research are studies of why women recruits—compared to men—fail to successfully complete basic training. To fill this empirical void, the current inquiry utilizes national-level data to examine the reasons women, compared to men, fail to complete academy basic training. Our results reveal statistically significant gendered differences in reasons for training non-completion by level of stress emphasized during training and type of academy affiliation that include voluntary withdrawal by recruits and non-voluntary withdrawal for failure to meet qualifying standards for physical fitness, firearms, and driving. The implications of these findings for police practice and research are discussed and recommendations are made.